Tidal Energy Ltd v Bank of Scotland plc [2014] EWCA Civ 1107. (December 2015) - Powley, Holly
Discussion of the Court of Appeal's decision in the Tidal Energy v Bank of Scotland case relating to the question of whether a customer had been taken to contract on the basis of standard banking practice with regard to the use of unique identifiers in a CHAPS transaction. Assesses the knowledge of the customer as to this issue and the importance of commercial common sense.